Demographic Characteristics and Ethical Issues of Disabled Patients who Applied at a Disabled Dental Care Center in Turkey (Annals of Medical Research, 2021)
Aim: This research was aimed to evaluate the demographic characteristics of the disabled patients who applied to the Disabled Dental Care Center (DDCC) at Faculty of Dentistry of Inonu University and the ethical issues that the dentists were faced with.
Keywords: Disabled Persons; Dental Care For Disabled; Ethics.